Optimization of Agrobacterium-mediated transformation of commercial heirloom tomato cultivars to develop novel traits via CRISPR/Cas9 genome editing - Jordan Oxendine; Elsa Ibarra-Reyes; Junchi Ma; Carrie Li; Sarah Baron; Allison E. Hwang; Ruiting Wang; Daniel Rodriguez-Leal (Planta, 2026)
Main conclusion Trait development for commercial heirloom tomatoes can be advanced by optimization of tissue culture and transformation via Agrobacterium and CRISPR/Cas9 mutagenesis. Abstract Genetic improvement using new genome editing approaches relies on the efficient delivery of the CRISPR/Cas system in the vegetable crop tomato. Previous protocols for tomato transformation have primarily focused on a handful of cultivars (M82, Ailsa Craig, Microtom, Sweet-100) with very little commercial relevance, and it is not clear if these protocols can be implemented directly in other commercially relevant varieties. Heirloom tomatoes are sought for their deep and diverse flavor but have not been subjected to systematic crop improvement via conventional breeding or biotechnology approaches such as transgenesis or genome editing. Therefore, we tested the transformation and regeneration capacity of six different heirloom cultivars known for their superior taste and market relevance in the US. Subsequently, we optimized rooting conditions and used the GRF4-GIF1 chimeric developmental regulator to successfully recover transgenic plants. Finally, we evaluated the efficiency of targeted genetic modification using the CRISPR/Cas9 genome editing system in several of these cultivars. We demonstrate that our optimizations led to successful transformation of several heirloom varieties, including the generation of edited plants for target genes modifying plant architecture and flowering time. Our results set the foundation for a biotechnology platform to deliver improved traits to local and regional heirloom varieties using genome editing.

The role of easily biodegradable organic materials as soil biostimulants in mediating the rapid enhancement of soil aggregate stability - Zheng MA; Xinlei ZHANG; Yujian WANG; Luyao YANG; Ruiting GUO; Longtao TU; Zhenlun LI (Pedosphere, 2026)

Construction of built-in electric field in Ru/Vo-NiCo2O4 heterostructure for efficient ethylene glycol oxidation reaction coupled nitrate to ammonia electrolysis - Jingwen Ma; Ruiting Wang; Jinhao Liu; Ying Tian; Junbin Li (Journal of Environmental Chemical Engineering, 2025)

The interaction between Ir nanocrystallites and Ni2P nanosheets regulates the adsorption energetics of intermediates for boosting ethanol electrolysis - Xiaoyu Zhang; Ruiting Chen; Ge Ma; Xin Wang; Yu Chen; Zhongwei Chen (Chemical Engineering Journal, 2025)

Preparation of AuSe-BNPs/CFME and its high-sensitivity simultaneous detection of caffeic acid and dihydrotanshinone I - Han Cheng; Yanbing Pan; Tao Fang; Uchkun Ishimov; Awais Ihsan; Abrar Hussain; Ruiting Tian; Wenwen Ma; Jun Li; Xianju Huang (Chemical Engineering Journal, 2025)

Polystyrene bead ingestion promotes atherosclerosis plaque progression via BMP signaling in mice - Na Yang; Bo Wu; Xiaoxue He; Junhu Ma; Longhao Dai; RuiTing Ma; Tingting Yang; Xiaoxi Ning; Xiaoyan Li; Shaobin Jia (Food and Chemical Toxicology, 2025)

Transcriptome Analysis Revealed Potential Immune-Related Genes of Head Kidney in the Yellow Catfish (Pelteobagrus fulvidraco) Challenged with Aeromonas hydrophila - Senhao Jiang; Yuting Lei; Ti Wang; Ruiting Ma; Chunqiang Hou; Qiuning Liu (Fishes, 2024)
Yellow catfish (Pelteobagrus fulvidraco) is an important freshwater fish species in aquaculture. However, as intensive farming has rapidly expanded, infectious diseases caused by various bacteria, such as Aeromonas hydrophila, have also increased. We conducted a transcriptomic analysis of head kidney from P. fulvidraco stimulated by A. hydrophila strain SHOU. A total of 43,249 unigenes with an average length of 1342 bp were obtained following assembly and annotation. By analyzing GO and KEGG enrichment, many differentially expressed genes (DEGs) and pathways related to immunity were identified. Out of the 973 DEGs that were identified, 553 were upregulated and 420 were downregulated. Moreover, KEGG enrichment analysis revealed that the innate immune system, including the TNF signaling pathway, NF-kappa B signaling pathway, and the Toll-like receptor signaling pathway involved in the defense, is activated against infectious response. Real-time quantitative reverse transcription-PCR (qRT-PCR) analysis demonstrated that immune response genes were upregulated in response to A. hydrophila stimulation compared to the control. In conclusion, this study provides valuable insights into the immune defense mechanism of P. fulvidraco and sheds light on the host immune genes involved in the response to bacterial infection.

Molecular Identification and Expression Analysis of an Intelectin Gene in the Yellow Catfish Pelteobagrus fulvidraco (Siluriformes: Bagridae) - Senhao Jiang; Yuting Lei; Yanxuan Li; Wanyan Sun; Ti Wang; Ruiting Ma; Qiuning Liu; Boping Tang (Fishes, 2023)
Intelectins (ITLNs) are a family of calcium-dependent lectins with carbohydrate-binding capacity, are distributed across various vertebrates, and play an important role in the innate immune response against pathogen infection. The yellow catfish Pelteobagrus fulvidraco (Siluriformes: Bagridae) is an economically important fish in China. The aim of this study was to quantify the gene expression of ITLN in response to pathogen-associated molecular patterns (PAMPs) stimulation. Here, the ITLN gene of P. fulvidraco was characterized and named PfITLN. The full-length cDNA of PfITLN was 1132 bp, including a 5’-untranslated region (UTR) of 140 bp, a 3’-UTR of 110 bp, and an open reading frame (ORF) of 882 bp encoding a polypeptide of 293 amino acids, which contains a signal peptide and two fibrinogen-related domains (FReDs). PfITLN had a molecular weight of 32.39 kDa with a theoretical pI of 5.03. The deduced PfITLN amino acid sequence had 81%, 64%, and 55% homology with Ictalurus furcatus, Danio rerio, and Homo sapiens, respectively. Moreover, the predicted tertiary protein structure of PfITLN was highly similar to that of other animals, and phylogenetic analysis showed that the PfITLN protein was close to those of other Teleostei. Real-time quantitative reverse transcription-PCR (qRT-PCR) analysis showed PfITLN expression in all examined tissues, with the highest abundance seen in the liver, followed by the head kidney, spleen, trunk kidney, and muscle. After PAMP infection with lipopolysaccharide (LPS) and polyriboinosinic polyribocytidylic acid (poly I:C), the expression levels of PfITLN were significantly upregulated at different time points. These results suggested that PfITLN might be involved in innate immunity.

Chitosan-based mussel-inspired hydrogel for rapid self-healing and high adhesion of tissue adhesion and wound dressings - Yongyan Yang; Ying Ma; Jingfei Wang; Liru You; Ruiting Zhang; Qingye Meng; Shuangling Zhong; Wenqi He; Xuejun Cui (Carbohydrate Polymers, 2023)